اثر ادارة المعرفة في تنمية القدرة على الابداع في مادة الرياضيات: دراسة تحليلية THE KNOWLEDGE MANAGEMENT IMPACT ON THE DEVELOPMENT OF CREATIVITY IN MATHEMATICS: AN ANALYTICAL STUDY. - Alhadidi, Ibrahim Ali Mubarak; Al-Hidabi, Dawood Abdulmalek Yahya (2019)
Mathematics Knowledge management; means the creation of organizational rules and strategies; collection of data and applied pure mathematical rules; knowledge of the subject matter and its storage, to improve the quality of mathematics teaching. The problem is that this has not been the applied in many schools, in a way that links knowledge management to the development of teachers' creative abilities in mathematics, when employ the implications of knowledge management in developing the capacity of mathematics teachers in creativity way. This was one of the reasons for the low level of student acquisition, when many find mathematics as a difficult subject. Through the analytical descriptive approach, the research reached several findings: the existence of a close correlation between the ability of mathematics teachers to innovate in the material, and their use of knowledge published by the knowledge management program. Knowledge management reduces errors in the teacher's procedural steps, enhance their ability to properly think about the subject matter, and enable him to solve the related problems. The use of cognitive schemes helps the teacher to innovate in teaching mathematical concepts; according to the methods and strategies used by the teacher in teaching these concepts. Stored charts help students interact, understand and connect concepts, and recognize the creative relationships between them.